Study of genetic polymorphisms and steady-state trough concentrations of imatinib and its active metabolite in predicting efficacy in gastrointestinal stromal tumors - Zhang, Menghua; Chen, Zhiyao; Liu, Xiaoxue; Zhou, Xiaojun; Miao, Liyan (Frontiers in Pharmacology, 2025)
The imatinib (IMA) steady-state trough concentration (Cmin) plays a critical role in the treatment outcomes of patients with gastrointestinal stromal tumors (GISTs), yet the effective concentration range in the Chinese population remains unclear. Additionally, few studies have investigated the effects of N-desmethyl imatinib (NDI) and genetic polymorphisms in metabolic enzymes and transporters on GIST treatment efficacy. Therefore, the aim of this study was to determine the value of the IMA and total (IMA + NDI) Cmin for the prediction of treatment outcomes in advanced GIST patients and to assess the influence of genetic polymorphisms on the IMA and total (IMA + NDI) Cmin and treatment efficacy. Twenty-one IMA-treated patients with advanced GIST were enrolled. An IMA Cmin ≥950 ng/mL and an IMA + NDI Cmin ≥956 ng/mL were associated with a reduced PD risk, with area under the receiver operating characteristic curve (AUC) values of 0.944 and 0.967, respectively. Higher IMA and IMA + NDI Cmin and higher risks of PD were observed in C allele carriers of rs2231137 and A allele carriers of rs2725252 in ABCG2 and in G allele carriers of rs2631372 in SLC22A5. In conclusion, the IMA and IMA + NDI Cmin can serve as effective indicators of advanced GIST treatment outcomes. Drug efficacy should be monitored in patients with an IMA Cmin <950 ng/mL or a total (IMA + NDI) Cmin <956 ng/mL. Furthermore, genetic polymorphism testing is recommended before dosing to appropriately adjust the IMA dose for carriers of the C allele in rs2231137, the A allele in rs2725252 in ABCG2, and the G allele in rs2631372 in SLC22A5.